International intervention in the Balkans since 1995 - Siani-Davies, Peter (Routledge, 2003)
"This volume offers an analysis of the activities of the international community in the Balkans since the 1995 Dayton Agreement. There has been substantial investment in the region but so far the gains have been limited and doubts remain as to the extent that sustainable security has been enhanced. There is a need for serious reassessment of policies and priorities, but this depends on a careful analysis of past successes and failures. The contributors seek to provide this by examining intervention, not just in terms of military action and the activities of major international agencies at state level, but also the activities of outside NGOs within the local environment."--Provided by publisher.
Keywords: North Atlantic Treaty Organization -- Armed Forces -- Yugoslavia.; Organisation du traité de l'Atlantique Nord -- Forces armées -- Yougoslavie.; North Atlantic Treaty Organization; Operation Allied Force, 1999.; National security -- Balkan Peninsula.; Yugoslavia -- History -- 1992-2003.; Balkan Peninsula -- History -- 20th century.; Opération Force alliée, 1999.; Yougoslavie -- Histoire -- 1992-2003.; Balkans -- Histoire -- 20e siècle.; HISTORY -- General.; Armed Forces; National security; Balkan Peninsula; Yugoslavia; Buitenlandse interventie.; Internationale betrekkingen.; 1900-2003; Electronic books.; History